Estrategia regional de formacion y capacitacion tecnia y professional. - Steward, Lucy (1990)
Outlines the regional strategy for technical and vocational training and development. This strategy was prepared by CARICOM member states in response to the need to establish a coherent approach to impart in an effective and efficient manner technical and vocational training.